2016
DOI: 10.5435/jaaos-d-16-00085
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm for Isolated Weber B Ankle Fractures: A Retrospective Review of 51 Nonsurgically Treated Patients

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
2
29
0
1
Order By: Relevance
“…With evaluation by weight-bearing radiographs, only three patients had MCS widening and the remainder were successfully treated non-operatively (4). Two case series have shown that when stability can be illustrated on weight-bearing radiographs, non-operative treatment can be expected to deliver good clinical outcomes (5,6). These studies provide evidence to support non-operative treatment as a cost containment strategy and to avoid the morbidity and complications known to be associated with operative management of these fractures.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…With evaluation by weight-bearing radiographs, only three patients had MCS widening and the remainder were successfully treated non-operatively (4). Two case series have shown that when stability can be illustrated on weight-bearing radiographs, non-operative treatment can be expected to deliver good clinical outcomes (5,6). These studies provide evidence to support non-operative treatment as a cost containment strategy and to avoid the morbidity and complications known to be associated with operative management of these fractures.…”
Section: Discussionmentioning
confidence: 92%
“…Because our patients were allowed to rest the healthy leg on the CT ring housing, and were allowed to use the two arm handles of the device for balance and support during the CT scan, true full weight bearing may not have been achieved. Other studies have demonstrated approximately 5-10% rate of instability demonstrated on weight-bearing radiographs, so it is estimated that it would take 10 to 20 patients to find 1 unstable fracture on weight-bearing CBCT scan (4,5). We recognize that by the nature of our study requiring our patients to bear weight on a fractured ankle, we may have selected the most stable of the ankles, which simply confirmed stability with the weight-bearing CBCT and limits the generalizability of the study results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 8 10 11 As radiografias nas incidências anteroposterior (AP), perfil e mortise (AP com 15° de rotação interna) são necessárias para confirmar o diagnóstico da fratura do tornozelo e avaliar a ocorrência de lesão da sindesmose mediante a identificação de alterações como fratura-avulsão da sindesmose, fratura alta da fíbula (Weber tipo C ou de Maisonneuve), abertura do espaço claro medial > 4mm, alterações da sobreposição e do espaço claro tibiofibular e a integridade do maléolo posterior. 7 12 A TAC auxilia na avaliação da posição relativa entre a tíbia e a fíbula, no melhor entendimento das fraturas do maléolo posterior possivelmente associadas e na realização do diagnóstico de fraturas ocultas. Em até 40% dos casos, o plano de tratamento pode mudar após estudo das imagens da TAC.…”
Section: Introductionunclassified